Experimental investigation and two-level model-based optimisation of a solar photovoltaic thermal collector coupled with phase change material thermal energy storage. (5th January 2021) - Lin, Wenye; Ma, Zhenjun; Wang, Shugang; Sohel, M. Imroz; Lo Cascio, Ermanno
Highlights: An air-based PVT collector coupled with a PCM TES unit was experimentally studied. A two-level model-based optimisation strategy was developed for PVT-PCM systems. Optimisation led to an optimal design and a performance map for optimal control. Optimisation improved the average efficiency to 39.7% and TES ratio to 72.7%. Abstract: This paper presents an experimental investigation of an air-based solar photovoltaic thermal (PVT) collector coupled with a centralised phase change material (PCM) thermal energy storage (TES) system, and the development of a model-based strategy to facilitate optimisation of the PVT-PCM systems. The originality of this study includes using statistical analysis to reveal the practical deficiencies of PVT-PCM systems, and orientating the system optimisation using a two-level model-based strategy. A set of experiments were designed and performed based on a lab-scale experimental facility to examine both electrical and thermal performance of the PVT-PCM system with various air flow rates, and different slopes and orientations of the PVT collector. The optimisation strategy was developed to identify the optimal design and at the same time to generate a performance map that can be used for control optimisation. The experimental results showed that there existed an optimal air flow rate for the PVT-PCM system under a given solar radiation for maximal overall system efficiency. To better utilise the PCM latent heat storage capacity, both the useful thermal energy generated from the PVT collector and the heat transfer within the TES unit need to be optimised. Compared to a baseline case without optimisation, the average overall system efficiency increased from 37.6% to 40.2%, and the average daily utilisation ratio of the latent TES capacity improved from 13.3% to 79.5%.